Hurdles for Starting Ministernotomy Aortic Valve Replacement Program - Nagre, Suraj Wasudeo (Journal of Cardiovascular Medicine and Cardiology, 2016)
Research article regarding hurdles for starting ministernotomy Aortic valve replacement program in Grant Medical College, Mumbai and techniques to overcome them. Here we studied twenty patients of aortic valve replacement surgery out of which ten are operated by ministernotomy and ten by full sternotomy in our institution, from May 2013 to May 2016.Middle age patients are selected out of which seven had regurgitant and three had stenotic lesion of aortic valve. Our observations are sternotomy time was more in initial cases but it decreased with experience. We faced difficulties in deairing heart and giving shock with routine internal shock paddles. It required special sterile external shock paddles. We required conversion to full sternotomy in two patients because heart continued to fibrillate even giving shock with paediatric internal shock paddles. CPB time, cross clamp time, CCU stay was same as compared to full sternotomy AVR patients. Cosmetically incision was better. Even with early difficulties and hurdles we continued our efforts to improve and succeeded in it. Ministernotomy AVR will always maintain its place in between full sternotomy AVR and minithoracotomy AVR.